Law and economics of Microsoft vs. U.S. Department of Justice - New paradigm for antitrust in network markets or inefficient lock-in of antitrust policy? - Marc-Peter Radke (Universität Hohenheim, 2001)
This paper contains an economic and legal analysis of the lawsuit Microsoft vs. U.S. Department of Justice beginning with the District Court's decision on June 7, 2000 up to the Proposed Final Judgement on November 6, 2001. I found that the courts' underlying economic paradigm regarding the assessment of monopoly power in 'New Economy Network Markets' was strongly influenced by BRIAN W. ARTHUR's theory of path dependence claiming (1) that high-technology markets being subject to network effects generally involve a danger of being locked-in to an inferior technology since winning or losing in a technology race is determined by small early random historical events and not by economic efficiency and (2) that there is almost no possibility to overcome inferior lock-in positions since network (compatibility) effects create insurmountable switching costs protecting the lock-in monopolist. As to Microsoft, it was often claimed that Macintosh would have been the better solution than Windows. The U.S. courts are convinced that rivals such as Linux wouldn't have any chance to overcome Microsoft's lock-in position without any antitrust intervention. However, I argue in accordance with opponents of ARTHUR's work that path dependence theory is only a theoretical curiosity that lacks empirical evidence. The predominance of a certain technology and especially the predominance of Windows in the operating system market is determined by economic efficiency and dominant market positions can be eroded very quickly by providing better quality. There is no empirical indication that network effects protect Microsoft's monopoly as it was claimed by the courts within their 'applications barrier to entry' theory. I claim that current interpretations of the U.S. antitrust law don't meet the requirements of fair competition rules in the 'New Economy'. If plaintiffs and the U.S. Department of Justice are victorious over Microsoft and lock-in theories become generally accepted by courts and market participants, further antitrust lawsuits are going to follow since most markets in the 'New Economy' are subject to network effects and high seller concentration. Strict antitrust policy could dampen economic growth due to investor uncertainty and the impossibility to take advantage of scale-based productivity effects.
urn:nbn:de:bsz:100-opus-4572
Keywords: K21; L12; L41; L43; L44; 330; Microsoft; antitrust; network effects; path dependence